EXPRESSION OF THE CONCEPT OF LOVE IN FARZONA'S POETRY (Scientific journal of the Fergana State University, 2025)
The concept of love in classical and modern literature is one of the themes without which it is impossible to find a work of art. In the poems of the master of modern Tajik poetry Farzona Khujandi, the concept of love has shown special characteristics, the understanding of which will help to correctly understand the poet's goals and intentions.